2017
DOI: 10.2458/v24i1.20979
|View full text |Cite
|
Sign up to set email alerts
|

Contesting energy transitions: wind power and conflicts in the Isthmus of Tehuantepec

Abstract: This article studies the expansion of large-scale wind energy projects on the Isthmus of Tehuantepec (Mexico) and local socio-environmental conflicts that have emerged in response. It explores how the neoliberal agenda in Mexico is shaping a specific way of implementing wind energy projects, and how this is leading to local resistance and the production of alternatives. The article is based on a historical analysis reconstructing the main features of wind power development, and pathways of struggle. By followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 56 publications
0
54
0
8
Order By: Relevance
“…Several studies in Mexico have located zones with suitable wind power, such as in the Baja California Peninsula, where it was found that the wind power density was above 400 W/m 2 [9]. Another study investigated the social impact caused by the expansion of large-scale wind energy projects on the Isthmus of Tehuantepec [10]. Furthermore, in the state of San Luis Potosi, a study of the installation of a hybrid PV-wind power generation system for social interest houses was validated [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in Mexico have located zones with suitable wind power, such as in the Baja California Peninsula, where it was found that the wind power density was above 400 W/m 2 [9]. Another study investigated the social impact caused by the expansion of large-scale wind energy projects on the Isthmus of Tehuantepec [10]. Furthermore, in the state of San Luis Potosi, a study of the installation of a hybrid PV-wind power generation system for social interest houses was validated [11].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on just one particular subsystem or technological innovation, without acknowledging the links with other domains runs the risk of overseeing negative effects on other sustainable development goals, as several examples show [59]. Thus, I argue, a national or even a global approach to transformations towards sustainability that takes into account different sectors, actors and levels and its linkages is paramount.…”
Section: From a Focus On Specific Systems To Holistic Transformationsmentioning
confidence: 99%
“…Innovations addressing a particular goal (let's say hunger) might negatively affect other goals (for example, life below water), but we hardly know how the different goals interact at different scales and in different subsystems [58,59]. In other words, thinking about system changes, radical social and institutional innovations, and new economic models [60] requires "advanced and comprehensive approaches" aimed at better understanding and governing system transformations toward sustainability [37].…”
Section: Innovation and Innovation Systems For Strong Sustainabilitymentioning
confidence: 99%
“…This "incentive-based system" is a reference to market-based environmentalism (Corson et al 2013;Dunlap 2017b), which after the Kyoto Protocol (1997) became the principal approach to mitigate climate change and biodiversity loss (Dunlap and Fairhead 2014). It is within this context that the Mareña Renovables wind project emerged, receiving loans from the United Nations Clean Development Mechanism (CDM) and Inter-American Development Bank (IBD) alongside investors from the Maquarie Group, Mitsubishi, FEMSA and the Dutch pension fund PGGM that sought to use the proposed energy to power Coca Cola, Heineken, Walmart and Grupo Bimbo among other shareholders (Avila-Calero 2017;Howe 2014;Smith 2012). Development of the Mareña began in 2004.…”
Section: Mareña Renovables Enters the Barramentioning
confidence: 99%
“…Wind energy development is primarily concentrated in the northern coastal Istmo. Neoliberal economic policy in Mexico, the Plan Puebla Panama/Mesoamerica (2001) industrial corridor, and green economic and climate change legislation have all paved the way for a "wind rush" in the region (Altamirano-Jiménez 2017;Avila-Calero 2017;Dunlap 2017b). Embraced by various elites across the political spectrum, wind energy became a means to wealth creation, and social, sustainable and collective development (Dunlap 2017b;Hamister 2012;Nahmad et al 2014;Simon 2013).…”
Section: Introductionmentioning
confidence: 99%